1983
DOI: 10.1111/j.1365-2230.1983.tb01792.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of immunofluorescence techniques in the diagnosis of bullous disorders: a review

Abstract: Immunofiuorescence (IMF) techniques are often of considerable help in the diagnosis of bullous disorders. It must be emphasized however, that they do not circumvent the need for routine skin histopathology. It is by considering the results of IMF and histopathology together that one is likely to avoid making diagnostic errors. As with routine skin histopathology, if the initial IMF findings are negative and the bullous disease is evolving or changing its clinical appearance, both histopathology and IMF tests s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
1
5
0
Order By: Relevance
“…The technique of immunofluorescence (IF) is widely used in the diagnosis of primary bullous diseases of the skin (PBD) and the methods and characteristic findings in various conditions have been reviewed recently (Black, Meyrick Thomas & Bhogal, 1983;Allen & Reeves, 1983)-We have used direct IF of skin biopsies and examination of sera by indirect IF throughout the last 9 years. Our initial experience in a series of no patients has been reported (Reeves et al, 1978) and we now present data obtained in a total of 279 consecutive patients, in order to review the value of IF in the investigation and management of PBD.…”
mentioning
confidence: 99%
“…The technique of immunofluorescence (IF) is widely used in the diagnosis of primary bullous diseases of the skin (PBD) and the methods and characteristic findings in various conditions have been reviewed recently (Black, Meyrick Thomas & Bhogal, 1983;Allen & Reeves, 1983)-We have used direct IF of skin biopsies and examination of sera by indirect IF throughout the last 9 years. Our initial experience in a series of no patients has been reported (Reeves et al, 1978) and we now present data obtained in a total of 279 consecutive patients, in order to review the value of IF in the investigation and management of PBD.…”
mentioning
confidence: 99%
“…[5] 1. Direct immunofluorescence (DIF): DIF is a one step procedure that involves application of fluoresceinated antibodies to a frozen section of the skin.…”
Section: Immunodermatological Methodsmentioning
confidence: 99%
“…Although DIF is the gold standard for the diagnosis of pemphigus the exact pemphigus subtype can be determined by histology of early vesicles. 7,9,10 A previous study by Diya et al found positive predictive value of 100% by DIF in the pemphigus group of disorders and negative predictive value of 85-90%. 1 In our study a positive predictive value of 100% and negative predictive value of 100% was found.…”
Section: Paraneoplastic Pemphigusmentioning
confidence: 94%